2015
DOI: 10.1016/j.atherosclerosis.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese lipid-lowering agent red yeast rice results in significant LDL reduction but safety is uncertain – A systematic review and meta-analysis

Abstract: RYR exerts a clinically and statistically significant reduction of 1.02 mmol/L LDL cholesterol. Only when the mild profile of adverse reactions can be affirmed in studies with adequate methodology for safety assessment, RYR might be a safe and effective treatment option for dyslipidemia and cardiovascular risk reduction in statin intolerant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 48 publications
6
92
0
5
Order By: Relevance
“…A recent meta-analysis in 2015 examined 20 randomized trials consisting of 6663 patients and showed a reduction in low density lipoprotein (LDL) cholesterol when comparing RYR to placebo groups (−1.02 mmol/L (−1.20, −0.83)); there was no difference in LDL between RYR and statin therapy (0.03 mmol/L (−0.36, 0.41)), with an incidence of kidney injury and liver abnormalities of less than 5% in both the RYR and control groups [7]. RYR has been demonstrated to not only improve lipid metabolism, but it can also reduce blood pressure, and may possess anti-inflammatory, antidiabetic, anticancer, and osteogenic properties [5].…”
Section: Red Yeast Rice As Nutraceuticalmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis in 2015 examined 20 randomized trials consisting of 6663 patients and showed a reduction in low density lipoprotein (LDL) cholesterol when comparing RYR to placebo groups (−1.02 mmol/L (−1.20, −0.83)); there was no difference in LDL between RYR and statin therapy (0.03 mmol/L (−0.36, 0.41)), with an incidence of kidney injury and liver abnormalities of less than 5% in both the RYR and control groups [7]. RYR has been demonstrated to not only improve lipid metabolism, but it can also reduce blood pressure, and may possess anti-inflammatory, antidiabetic, anticancer, and osteogenic properties [5].…”
Section: Red Yeast Rice As Nutraceuticalmentioning
confidence: 99%
“…Statins are metabolized by Cytochrome P450 (CYP) enzymes, and the administration of RYR with CYP enzyme inhibitors (e.g., ketoconazole, human immunodeficiency virus (HIV) protease inhibitors, erythromycin) can lead to worsening undesirable adverse effects, such as myopathy [5,17]. Nonetheless, the clinical studies that showed the effectiveness of RYR in dyslipidemia also demonstrated that it is a relatively safe product [7,18]. …”
Section: Red Yeast Rice As Nutraceuticalmentioning
confidence: 99%
“…En metaanalyse viste at behandling med rød gjaeret risekstrakt reduserte LDL-kolesterolninvået med 1,0 mmol/l i forhold til placebo -effekten var lik lave doser av statiner (16). Forfatterne fant manglende rigorøs og omfattende overvåkning av bivirkninger i disse studiene sammenlignet med vanlige …”
Section: Rød Gjaeret Risekstraktunclassified
“…dokonali oceny skuteczności oraz bezpieczeństwa stosowania preparatów RYR, przeprowadzając metaanalizę 20 randomizowanych badań klinicznych obejmujących 6663 pacjentów [23]. Dawka RYR stosowana w poszczególnych badaniach wynosiła 1200-4800 mg/ /dobę, co odpowiadało 4,8-24 mg monakoliny K. W badaniach kontrolowanych placebo średnia redukcja stężenia cholesterolu wynosiła 39,4 mg/dl (1,02 mmol/l), redukcja stężenia TG wyniosła 23 mg/dl (0,26 mmol/l), zanotowano również niewielki wzrost stężenia HDL-C o 2,7 mg/dl (0,07 mmol/l).…”
Section: Monakolina -Od Starożytności Do Współczesnościunclassified